Establishing microbial baselines to identify indicators of coral reef health - Glasl, Bettina (2018)
Microorganisms make a significant contribution to reef ecosystem health and resilience via their critical role in mediating nutrient transformations, their interactions with macro-organisms and their provision of chemical cues that underpin the recruitment of diverse reef taxa. However, environmental changes often cause compositional and functional shifts in microbial communities that can have flow-on consequences for microbial-mediated processes. These microbial alterations may impact the health of specific host organisms and can have repercussions for the functioning of entire coral ecosystems. Assessing changes in reef microbial communities should therefore provide an early indicator of ecosystem impacts and would underpin the development of diagnostic tools that could help forecast shifts in coral reef health under different environmental states. Monitoring, management and active restoration efforts have recently intensified and diversified in response to global declines in coral reef health. Here we propose that regular monitoring of coral reef microorganisms could provide a rapid and sensitive platform for identifying declining ecosystem health that can complement existing management frameworks. By summarising the most common threats to coral reefs, with a particular focus on the Great Barrier Reef, and elaborating on the role of microbes in coral reef health and ecosystem stability, we highlight the diagnostic applicability of microbes in reef management programs. Fundamental to this objective is the establishment of microbial baselines for Australia's coral reefs.